The effects of the electroless copper coating to the thermal expansion behaviors of silicon carbide particles reinforced copper matrix composites for the electronic packaging applications - Azmi Kamardin (School of Materials Engineering, 2013)
The thermophysical properties of Cu-SiCp composites can be optimized by improving the bonding between the copper matrix and SiCp reinforcement. This can be done via an electroless coating process.